EVALUASI SISTEM INFORMASI PERSEDIAAN PADA CV. SARANA TELEMAXINDO - Nelly, Nelly; Stevanus, Stevanus; Rosna, Rosna; Haryono, Ivan (CommIT (Communication and Information Technology) Journal, 2010)
Evaluation objectives of inventory information systems at CV. Facilities Telemaxindo was to evaluate the weaknesses of the implementation of internal control, as well as estimating and assessing possible risks that might arise. The research method used is literature study of reference books in the library, and field study consisted of observation, interviews with relevant parties, creating check lists, check the inventory information systems documentation, and testing of inventory application systems. The results are findings of control weaknesses in the implementation of security management, operational management control, boundary control, input control, and output control on the present inventory information system. These weaknesses could pose a risk and if not dealt soon it could hurt the company. The resulting conclusion of the security management control, boundary control, control input, and output control is not running well so that it needs to be improved in accordance with the recommendations, while operational management control has been running fairly well.Keywords: evaluation, information system, inventory